1992
DOI: 10.1111/j.1540-8159.1992.tb03056.x
|View full text |Cite
|
Sign up to set email alerts
|

Atrial Paralysis in a Patient with Emery‐Dreifuss Muscular Dystrophy

Abstract: Emery-Dreifuss disease is a benign X-linked muscular dystrophy characterized by a distinct pattern of muscle weakness, which is of insidious onset and slow progression. It is associated with atrial paralysis that results in sudden death in early adulthood if left untreated. The authors report the documentation of electrical and mechanical silence confined to the atria in a patient with this disease. Electrocardiography and electrophysiological study document the absence of electrical atrial activity, and inabi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
3

Year Published

1995
1995
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 10 publications
0
6
0
3
Order By: Relevance
“…Patients with that electrophysiological condition require a VVI pacemaker implantation or reprogramming of a pre-existing CIED into a VVI mode. Electrical atrial silence heralds a decline in atrial haemodynamic function [18,19]. Electrical silence shown in a surface ECG trace needs to be verified during the procedure, as was done in this case.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with that electrophysiological condition require a VVI pacemaker implantation or reprogramming of a pre-existing CIED into a VVI mode. Electrical atrial silence heralds a decline in atrial haemodynamic function [18,19]. Electrical silence shown in a surface ECG trace needs to be verified during the procedure, as was done in this case.…”
Section: Discussionmentioning
confidence: 99%
“…Ryzyko wystąpienia zaburzeń rytmu i przewodzenia zwiększa się z wiekiem [1,2]. Początkowo mogą być to tylko bradykardia zatokowa, zahamowania zatokowe czy pojedyncze pobudzenia przedwczesne przedsionkowe, w późniejszym okresie występują tachyarytmie nadkomorowe (częstoskurcz nadkomorowy [SVT, supraventricular tachycardia], migotanie przedsionków [AF, atrial fibrillation]).…”
Section: Wstępunclassified
“…Początkowo mogą być to tylko bradykardia zatokowa, zahamowania zatokowe czy pojedyncze pobudzenia przedwczesne przedsionkowe, w późniejszym okresie występują tachyarytmie nadkomorowe (częstoskurcz nadkomorowy [SVT, supraventricular tachycardia], migotanie przedsionków [AF, atrial fibrillation]). Dla pacjentów z dystrofią mięśniową Emery'ego-Dreifussa charakterystyczny jest brak czynności elektrycznej przedsionków (atrial standstill, atrial paralysis) spowodowany włóknieniem mięśniówki przedsionków, a także układu bodźco-przewodzącego [2,3]. Choroba może być dziedziczona w sposób sprzężony z płcią lub autosomalnie dominująco; zależnie od typu dominują, odpowiednio, zaburzenia przewodzenia lub komorowe zaburzenia rytmu serca [4,5].…”
Section: Wstępunclassified
“…[2]- [3] In the past three decades, atrial standstill phenotype is rarely reported to develop in all forms of EDMD inheritance. [5]- [8] Case Report…”
Section: Introductionmentioning
confidence: 99%
“…[5]- [8] Lamin A/C gene consists of 12 exons that produce at least four types of RNA via alternate splicing including lamins A,Aδ10, C and C2. Lamin A and C are intermediate filament proteins that form HGVS guidelines; http://www.hgvs.org/mutnomen/) [ Figure 3].…”
Section: Introductionmentioning
confidence: 99%